Wnt3a promotes odonto/osteogenic differentiation in vitro and tertiary dentin formation in a rat model. (19th January 2023) - Sukarawan, Waleerat; Rattanawarawipa, Panarat; Yaemkleebbua, Kamonwan; Nowwarote, Nunthawan; Pavasant, Prasit; Limjeerajarus, Chalida Nakalekha; Osathanon, Thanaphum
Abstract: Aim: To investigate the effect of Wnt3a on odonto/osteogenic differentiation of stem cells isolated from human exfoliated deciduous teeth (SHEDs) and reparative dentine formation in a rat model. Methodology: Stem cells isolated from human exfoliated deciduous teeth were cultured in media with Wnt3a (50–200 ng/ml). Wnt activation was confirmed by β‐catenin immunocytochemistry. Colony‐forming unit assay (normalized percentage area), osteogenic gene expression analysis by real‐time polymerase chain reaction and mineralization assays measured by the absorption at 540 nm were performed. Tertiary dentine formation in vivo was evaluated using 8‐week‐old, male Wistar rats. Cavities with pinpoint pulp exposure by a sharp instrument were prepared at the mesial surface of the first molars. Teeth were divided into ( n  = 6): (1) distilled water (negative control), (2) phosphate‐buffered saline (PBS), (3) lithium chloride in DI (20 μM), and (4) Wnt3a in PBS (200 ng/ml). Collagen sponge was used as a scaffold. The cavity was sealed with glass ionomer restoration. Four weeks later, animals were euthanized by sodium pentobarbital (120 mg/kg body weight). Hard tissue formation was evaluated using micro‐computerized tomography. Sixty consecutive slides from the initial plane were analysed and calculated as bone/dentine volume per total tissue volume. Paraffin sections (2 μm) were stained with haematoxylin and eosin and Masson's trichrome for morphological evaluation. Data are presented as the mean ± standard error. Mann–Whitney U test was used for two‐group comparison. Kruskal Wallis followed by pairwise comparison was employed for three or more group comparisons. Statistical analysis was performed using GraphPad Prism 7. Differences were considered significant at p  < .05. Results: Wnt3a decreased SHEDs colony formation and increased OSX, BMP2, and DMP1 expression, corresponding to an increase in mineralization. Additionally, a significant increase in dentine/bone volume per total tissue volume was observed in Wnt3a treated defects. Dentine bridge formation at the exposure sites treated with Wnt3a demonstrated, while fibrous tissues were observed in the control. Conclusions: Wnt3a suppressed proliferation, increased osteogenic differentiation of SHEDs and promotes tertiary dentine formation. Wnt3a could be utilized as biological molecule for vital pulp therapy.